The Death of God in Sartre's The Flies - Malek J. Zuraikat; Sarah Mashreqi (Acta Scientiarum. Language and Culture, 2020)
The death of god, which refers to the absence of god's value, weight, significance, and role from people's life experience, is among the most dominant themes of existential literature, especially that of Sartre. It is heavily investigated in his theoretical as well as creative works, such as Being and Nothingness (1969) and The Flies (1989) as it constitutes the cornerstone of his philosophical views of Existentialism, nihilism, freedom, and responsibility. It is hard to understand Sartre's The Flies (1989) and its philosophical background as well as theme(s) without considering the concept of the death of god and its involvement in the development of actions. Accordingly, this paper reads The Flies (1989) investigating Sartre's techniques of introducing and contending that god is dead and has nothing to do with people's life or prosperity. Considering the related literature and the different perspectives of Nietzsche and Hegel regarding Existentialism, the paper deciphers certain scenes and speeches delivered by several characters, such as Zeus, Orestes, and Electra, and it concludes that Sartre’s The Flies (1989) shows how the belief in the death of god may function as a productive force in humans' life and existence. Thus, the paper may help readers of Sartre better understand the existential mechanism of the death of god and comprehend why Sartre's Existentialism is to be viewed as an optimistic, rather than pessimistic, approach.